Effects of exercise on patients with vascular cognitive impairment based on ACSM recommendations: a systematic review of randomized controlled trials - Ye, Yu; Wu, Kairui; Xu, Fangyuan; Li, Hongtao; Li, Xuejun; Hu, Peijia; Cheng, Hongliang (Journal of neurology, 2025)
Background Exercise is considered to be an effective method for functional recovery in patients with vascular cognitive impairment (VCI), but there is a paucity of research on exercise dosage. There has been no meta-analysis of the effects of exercise therapy for vascular cognitive impairment based on the American College of Sports Medicine (ACSM) exercise prescription for a seemingly healthy population. We therefore conducted a study to analyze the effects of various exercise therapies on cognitive functioning, physical functioning, and ability to perform activities of daily living in patients diagnosed with vascular cognitive impairment. Methods Four electronic databases, namely PubMed, Embase, Web of Science, and Cochrane, were systematically searched for studies examining the effects of exercise on patients with VCI. The exercise interventions were categorized into an ACSM high adherence group versus an ACSM low or indeterminate adherence group, following the recommendations for exercise testing and prescribing for seemingly healthy populations developed by ACSM. Meta-analyses were conducted using a random effects model to compare results among subgroups. Results The study encompassed 14 trials involving 1333 subjects. Among these, 8 studies adhered highly to ACSM recommendations, while 6 studies demonstrated low or uncertain adherence. Subgroup analyses revealed differing effects: in the high adherence group, SMDs for cognitive functioning, living ability, and physical functioning were 0.53 (95% CI 0.13–0.94), 0.53 (95% CI 0.11–0.94), and 0.66 (95% CI 0.45–0.87), respectively. Conversely, in the low or indeterminate adherence group, SMDs for cognitive functioning, living ability, and physical functioning were 0.09 (95% CI − 0.13 to 0.32), − 0.11 (95% CI − 0.57 to 0.34), and 0.65 (95% CI − 0.04 to 1.35). We performed subgroup analyses by type of vascular cognitive impairment, and meta-analyses showed positive SMDs of 0.59 (95% CI 0.22–0.97) and 0.68 (95% CI 0.47–0.90) for exercise on cognitive impairment after stroke in terms of cognitive function and physical function, respectively. Conclusion The results suggest that exercise interventions exhibiting high adherence to ACSM guidelines yield more favorable outcomes concerning cognitive functioning, physical functioning, and daily living abilities among patients with VCI compared to interventions with low or uncertain adherence to ACSM recommendations.